ANALGESIA PREEMPTIVA COM CLORIDRATO DE TRAMADOL EM OVARIOHISTERECTOMIA DE CADELAS - Cruz, Pâmela d. L. T. d.; Rodrigues, Cláudia M.; Rakoski, Andréia S.; Amaral, Bruna P.; Müller, Daniel C. d. M.; Lukarsewski, Rafael (Salão do Conhecimento, 2013)
Resumo